Association between nitric oxide and cancer and stroke risk: A meta-analysis - Abdul Rohim, Tualeka; Juliana Jalaludin, Tualeka; Gasana, Janvier; Nor Ashikin, Sopian; Chao, How Ran; Mohd Yusmaidie, .; Velu, Perumal; Suardi, Zurimi; Pudji, Rahmawati; Ahsan, Ahsan; Salsabila, Novianti (F1000 Research Ltd., 2023)
Background: Numerous case-control studies have been carried out to test the mechanism by which nitric oxide, specifically the polymorphism 894G>T in the eNOS gene, or endothelial nitric oxide synthase, raises the possibility of stroke and cancer. Methods: The aim of this meta-analysis was to describe the correlation between cancer and stroke risk with nitric oxide, by implementing a comprehensive search in various digital databases, including Science Direct, PubMed, and Google Scholar, in the period 2012-2023 to observe the published results of all related studies. Results: The meta-analysis included a total of fifteen case-control studies. These studies involved 3,019 cases and 3,333 controls in total. This study found that the GG versus GT+TT genotype of eNOS 894G>T polymorphism was significantly positively correlated with cancer risk. Additionally, the significance of this association was further attributed to the specific type of polymorphism involved, as well as the risk of stroke in the T versus G model, followed by TT versus GG+GT. Conclusions: The results of the eNOS 894G>T polymorphisms have been correlated with cancer, and in particular, the GT+TT versus GG model yielded an odds ratio (OR of 1.96, a 95% CI of 1.22 to 3.15, and a p-value of 0.0005. Moreover, the mentioned polymorphisms were found to be associated with stroke risk in the T versus G model, which had an OR of 1.20; 95% CI of 1.01 to 1.43 with a p-value of 0.04; and TT versus GG+GT with an OR of 0.09; 95% CI of 0.03 to 0.30 with a p-value of 0.0001.